COMPREHENSIVE ANALYSIS OF NUTRITIONAL INTERVENTIONS IN CHRONIC DISEASE MANAGEMENT: ROLE OF GENERAL NUTRITION SPECIALISTS IN IMPROVING HEALTH OUTCOMES - 1Mohammed Ahmed Ali Almashham, 2Abdullah Ali Saleh Balhareth, 3Saeed Hassan ALZabadin, 4Salem Hashan Almunajjim 5Ali hamad ali Al abas, 6Mohammed Mahdi Ali Jali, 7Samer Mahdi Ali Al-Makayil, 8Mansour Mahdi Abdullah Al Abbas, (Chelonian Research Foundation, 2022)
Nutritional interventions play a crucial role in managing chronic diseases, contributing significantly to improved health outcomes. This article comprehensively surveys the role of familiar nutritionists in unremitting malady administration. Broad investigates various dietary changes, counting dietary alterations, supplements, and way of life changes. This arrangement depicts the strategies utilized in this test, the collection of information, and the planning of the test. The findings in numbers, tables, and charts illustrate the benefits of tallying calories in lessening infection and improving well-being. The introduction clarifies the suggestions from these findings and emphasizes the significance of joining clinical information into clinical hone. Finally, advancements in joining nutritional abilities into continuous malady administration programs are prescribed to achieve superior outcomes. Keywords: nutritional interventions, chronic disease management, general nutrition specialists, health outcomes, dietary modifications, supplementation, lifestyle changes.